Effects of 3 Topical Plant Extracts on Wound Healing in Beef Cattle - Lipinski, Leandro Cavalcante (African Networks on Ethnomedicines, 2012)
Eleven heifers of the Purunã cattle breed were used to evaluate wound healing by second intention. An experimental wound excision model in bovines was created by means of a skin punch of diameter 2cm. The animals were topically treated for 17 days with a saline control or decoctions of Schinus terebinthifolius Raddi (Aroeira mansa), Tabebuia avellanedae Lorentz ex Griseb (Ipê Roxo), and Casearia sylvestris Sw.(Guaçatonga) mixed with carboxymethyl cellulose. Centripetal retraction, clinical, and histological aspects of the wounds were observed until complete healing. Decoctions of T. avellanedae and S. terebinthifolius, but not C. sylvestris, had a beneficial effect on wound healing by second intention.